KAJIAN SALURAN IRIGASI TERSIER DI DESA PERCUT DAERAH IRIGASI BANDAR SIDORAS KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG (Study of Tertiary Irrigation Channel in Percut Village in the Irrigation Areas of Bandar Sidoras Percut Sei Tuan District of Deli - Muhammad Prawira; Sumono Sumono; Taufik Rizaldi (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT The need of water on the field of percut village was channeled through tertiary canal that made from soil and concrete. Soil channel can affect the lossing of water through evapotranspiration, percolation and seepage so that the efficiency of water distribution is low. This study was aimed to examine the tertiary irrigation channel in percut village in the irrigation areas of Bandar Sidoras percut sei tuan district of deli serdang. The results of the research showed the efficiency of the distribution on channel I at a distance of 50 m was 35.03%, on channel II at a distance of 50 m was 14.82% and on a concrete channel at a distance of 50 m was 80.23%. The average flow velocity was smaller than the critical speed so that precipitation happened, there for a redesign of the channel dimensions was needed. The result of the best design of tertiary channel dimensions for the channel I was 0.66 m width (B) and depth (D) was 0.14 m with a slope of 0.015%,  for channel II the width (B) was 0.81 m and the depth (D) was 0.19 m with a slope of 0.02%, while for concrete channel the width (B) was 0.67 m and the depth (D) was 0.36 m with a slope of 0.02%. Key Word : Tertiary A Channel, Conveyance Efficiency, Design Of Canals ABSTRAK Kebutuhan air pada lahan persawahan di Desa Percut disalurkan melalui saluran tersier yang terbuat dari saluran tanah dan saluran beton. Pada saluran tanah dapat mengakibatkan terjadinya banyak kehilangan air melalui evapotranspirasi, perkolasi dan rembesan sehingga efisiensi penyaluran air menjadi rendah. Penelitian ini bertujuan untuk mengkaji saluran irigasi tersier di Desa Percut Daerah Irigasi Bandar Sidoras Kecamatan Percut Sei Tuan Kabupaten Deli Serdang.Hasil penelitian ini menunjukkan nilai efisiensi penyaluran pada saluran I dengan jarak 50 meter adalah 35,03%, saluran II dengan jarak 50 meter adalah 14,82% dan saluran beton dengan jarak 50 meter adalah 80,23%. Kecepatan aliran rata-rata lebih kecil dari kecepatan kritis sehingga terjadi pengendapan, untuk itu perlu rancangan ulang terhadap dimensi saluran. Hasil rancangan dimensi saluran tersier yang terbaik untuk saluran I adalah lebar saluran (B) 0,66 m dan kedalaman (D) 0,14 m dengan kemiringan 0,015%, untuk saluran II yaitu lebar saluran (B) 0,81 m dan kedalaman (D) 0,19 m dengan kemiringan 0,02%, sedangkan untuk saluran beton yaitu lebar saluran (B) 0,67 m dan kedalaman (D) 0,36 m dengan kemiringan 0,02%.   Kata Kunci : Saluran Tersier, Efisiensi Penyaluran, Perancangan Saluran